(untitled) (Tribhuvan University Journal of Microbiology, 2018)
Objectives: This study aimed to study the prevalence and antibiotic susceptibility pattern of methicillin-resistant Staphylococcus aureus (MRSA) isolated from clinical specimen. Methods: During the study period (April-September, 2013), 754 various clinical samples collected from patients visiting at Alka Hospital were cultured for isolation of S. aureus. The isolates were characterized as S. aureus by their morphology on Gram staining, growth characteristics and coagulase production. Screening of methicillinresistant S. aureus was determined using cefoxitin disk as recommended by Clinical Laboratory Standard Institute. The diameter of the zone of inhibition was measured and interpretation was done in accordance with the CLSI guidelines. An isolate was considered to be a MRSA strain if cefoxitin inhibition zone diameter was < 22 mm. All isolates were subjected to antimicrobial susceptibility testing by modified Kirby Bauer disc diffusion methods. Results: Total 109 (14.46%) isolates were confirmed as S. aureus and 36 (33.02%) S. aureus isolates of them were screened as methicillin resistant S. aureus. Maximum percentage (63.9%) of methicillin resistant S. aureus strains were comprised of pus specimens. Highest percentage (47.6%) of MRSA was isolated from the age group of above 60 years. Maximum percentage of MRSA strain was detected in admitted patients which accounts for 63.9% of total MRSA. Majority of MRSA isolates were observed to be multidrug resistant. All 36 isolates of MRSA showed that vancomycin, a reserved drug for the multidrug resistant MRSA found to be 100% sensitive. Beside vancomycin, ceftriaxone (83.3%) found to be most sensitive drug for the MRSA isolates. Conclusion: The emergence of drug resistance and its dissemination in MRSA is worrisome. So we need to develop newer agents as well as slow down the spread of resistant strains by various control measures.